2015
DOI: 10.1007/s11126-015-9349-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Whole Brain Radiotherapy on Social Cognition and Association with Hippocampal and Frontal Dosimetry

Abstract: The influence of brain radiotherapy on neurocognition is a major concern. Social cognition is a mental process in the meaning of social interaction and the recognition of facial emotion is a domain of social cognition. Thus, we aimed to investigate the early effect of whole brain radiotherapy on facial emotion recognition ability. Thirteen patients with various brain tumors in the study. Beck depression and anxiety inventory and the facial emotion recognition test by using a set of photographs were performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Concerning studies with more than one assessment, to the best of our knowledge only one study assessed influences of an oncological treatment other than surgery. This study reported changes in emotion recognition after radiation [130]. Studies using two time points before and after surgery reported on a performance decrease in emotion recognition in glioblastoma patients [122] as well as region specific impairments of sociocognitive functioning [84] in a heterogeneous group of brain tumor patients.…”
Section: Sociocognitive Functioningmentioning
confidence: 86%
See 2 more Smart Citations
“…Concerning studies with more than one assessment, to the best of our knowledge only one study assessed influences of an oncological treatment other than surgery. This study reported changes in emotion recognition after radiation [130]. Studies using two time points before and after surgery reported on a performance decrease in emotion recognition in glioblastoma patients [122] as well as region specific impairments of sociocognitive functioning [84] in a heterogeneous group of brain tumor patients.…”
Section: Sociocognitive Functioningmentioning
confidence: 86%
“…By contrast, other studies pointed to significantly impaired sociocognitive functioning even before any treatment has started in brain tumor patients [88,94]. Likewise, some posttreatment studies reported relevant impairments [87,118,122,130], some regionspecific [80,95,101] (e.g., mainly frontal and insular regions). By contrast, other investigations reported no clinically relevant or only minor impairment of sociocognitive functioning in brain tumor patients even after treatment [81,96,98,111,120,127].…”
Section: Summary Of Main Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…Data on social cognition in patients with brain tumors, particularly whether there are changes after treatment, are limited [8]. One prior small study evaluated changes in emotion recognition after whole brain RT [56], and studies have shown performance decreases in patients with glioblastoma [57] and varied brain tumors [58] after surgery. There is a critical need to mechanistically study the impact of cranial RT on social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits have been reported in adult brain tumor survivors (who survived >6 months) with an incidence rate of 50% to 90% after partial-or whole-brain irradiation (1)(2)(3). The cognitive impairments induced by RT are marked by reduced verbal memory, spatial memory, attention, and novel problem-solving abilities (4)(5)(6). Clinically, irradiationinduced brain injury is classified as acute (days to weeks), early delayed (1-6 months), and late delayed (>6 months) (7).…”
Section: Introductionmentioning
confidence: 99%